Scaling up the use of low-emissions development (LED) research outputs in Colombia: Linking science to policy for supporting country’s LED agriculture - Khatri-Chhetri, Arun; Bohórquez Lozano, Viviana; Martínez Barón, Deissy; Wollenberg, Eva Karoline (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Key messages – National greenhouse gas (GHG) inventories can be improved to achieve Colombia’s nationally determined contribution (NDC) target and support low-emissions development (LED) agriculture by reducing uncertainties in emission calculations using activity data for fertilizer application and estimates of emission reduction potentials from cacao plantations. – Co-design of LED research outputs (i.e., activity data for fertilizer emission estimates and GHG mitigation potential of cacao plantations) and evaluation of their impact pathway with users ensures scaling up the use of outputs by implementing key actions along the impact pathway. – Communication, engagement, and capacity- strengthening for the use of activity data for fertilizer emission estimates and GHG mitigation potentials of cacao plantations are key components of scaling research outputs and generating impacts.